Pengaruh auditor dan rasio keuangan terhadap managemen laba - AGUSTIN YULIANA; ITA TRISNAWATI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
This study aims to get empirical evidence that the effect big four auditor, specialist auditor, audit tenure return on asset, market to book value ratio, leverage, firm size, operating cash flow and loss on earnings management. The sample used in this research was the secondary data from annual report of manufacturing companies which listed on Indonesia Stock Exchange in 2011-2013. The sample was taken using purposive sampling method. The results provide evidence that return on asset, leverage, firm size, operating cash flow and loss are influence the earnings management. Nonetheless, big four auditor, specialist auditor, audit tenure and market to book value ratio are not influence the earnings management.